Penerapan Media Pembelajaran STAVOL untuk Meningkatkan Pemahaman Peserta Didik dalam Pembelajaran Matematika Materi Pengukuran Volume pada Kelas IV UPT SD Negeri Penataran 04 - Yensia Prarisma Nur Sahara; Arina Restian (Jurnal Sekolah Dasar, 2023)
This study aims to analyze and describe the application of STAVOL learning media to improve students' understanding in learning Mathematics of Volume Measurement Materials in class IV UPT SD Negeri Penataran 04. This study used Classroom Action Research with class IV subjects consisting of 12 people with various abilities. The instruments used are LKPD which is done in groups and Evaluation Sheet which is done independently. Based on the analysis of the results of the research and the previous discussion, it shows that the results of the test for understanding the material for measuring the volume of class IV students as a whole obtained 50% of high-ability students (score ≥ 80) with a total of 6 students, 33% of moderate-ability students (scores ≥ 65 and < 80) with a total of 4 students, as well as 17% low ability students (score < 65) with a total of 2 students. So it can be interpreted that the analysis of the application of STAVOL learning media to increase students' understanding in learning Mathematics material on volume measurement in class IV is a variety of students with high, medium, and low abilities.